circUBE2G1 interacts with hnRNPU to promote VEGF-C-mediated lymph node metastasis of lung adenocarcinoma - Li, Yuting; Chen, Hui; Zhao, Yue; Yan, Qilu; Chen, Lulu; Song, Qibin (Frontiers in Oncology, 2024)
BackgroundPatients with lymph node(LN)metastasis-positive Lung adenocarcinoma(LUAD)suffer from a significantly reduced five-year survival rate. Increasing evidence indicates circular RNAs(circRNAs)play crucial roles in regulating cancer progression. However, the specific regulatory mechanisms of circRNAs in the LN metastasis of LUAD have not been fully explored.MethodsGEO datasets and sequence analysis were applied for the identification of differentially expressed circRNAs between LUAD tissues and adjacent normal tissues. In vitro and in vivo experiments were performed to evaluate the function of circUBE2G1. The interaction between circUBE2G1 and VEGF-C was determined by RNA pulldown, ChIP, ChIRP and luciferase assays.ResultsIn this study, we identified a novel circRNA, circUBE2G1 (hsa_circ_0041555), which is upregulated in LUAD and positively correlated with LN metastasis in patients with LUAD. Functionally, overexpression of circUBE2G1 promotes lymphangiogenesis and LN metastasis of LUAD both in vitro and in vivo. Mechanistically, circUBE2G1 activates the transcription of vascular endothelial growth factor C (VEGF-C) by recruiting hnRNPU to enhance H3K27ac on the VEGF-C promoter, thereby facilitating lymphangiogenesis and LN metastasis in LUAD.ConclusionOur findings offer new insights into the mechanisms behind circRNA-mediated LN metastasis in LUAD and suggest that circUBE2G1 may serve as a potential therapeutic target for LN metastasis in LUAD.